Differential requirements for DNA repair proteins in immortalized cell lines using alternative lengthening of telomere mechanisms. Issue 8 (31st May 2017) - Martinez, Alaina R.; Kaul, Zeenia; Parvin, Jeffrey D.; Groden, Joanna
Abstract: Cancer cells require telomere maintenance to enable uncontrolled growth. Most often telomerase is activated, although a subset of human cancers are telomerase‐negative and depend on recombination‐based mechanisms known as ALT (A lternativeL engthening ofT elomeres). ALT depends on proteins that are essential for homologous recombination, including BLM and the MRN complex, to extend telomeres. This study surveyed the requirement for requisite homologous recombination proteins, yet to be studied in human ALT cell lines, by protein depletion using RNA interference. Effects on ALT were evaluated by measuring C‐circle abundance, a marker of ALT. Surprisingly, several proteins essential for homologous recombination, BARD1, BRCA2, and WRN, were dispensable for C‐circle production, while PALB2 had varying effects on C‐circles among ALT cell lines. Depletion of homologous recombination proteins BRCA1 and BLM, which have been previously studied in ALT, decreased C‐circles in all ALT cell lines. Depletion of the non‐homologous end joining proteins 53BP1 and LIG4 had no effect on C‐circles in any ALT cell line. Proteins such as chromatin modifiers that recruit double‐strand break proteins, RNF8 and RNF168, and other proteins loosely grouped into excision DNA repair processes, XPA, MSH2, and MPG, reduced C‐circles in some ALT cell lines. MSH2 depletion also reduced recombination at telomeres as measured by intertelomeric exchanges. Collectively, the requirement for DNA repair proteins varied between the ALT cell lines compared. In sum, our study suggests that ALT proceeds by multiple mechanisms that differ between cell lines and that some of these depend on DNA repair proteins not associated with homologous recombination pathways.